2004
DOI: 10.1093/jn/134.7.1827
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavones Improve Spatial Delayed Matching-to-Place Performance and Reduce Cholinergic Neuron Loss in Elderly Male Rats

Abstract: To investigate the protective activity of soy isoflavones on neurons, the effects of isoflavones on cholinergic enzyme activity, immunoreactivities of cholinergic enzyme, and delayed matching-to-place (DMP) performance were measured in normal elderly rats. Male Sprague-Dawley rats (n = 48; 10 mo old) were assigned to 3 groups: CD (control diet), ISO 0.3 (0.3 g/kg soy isoflavones diet), and ISO 1.2 (1.2 g/kg soy isoflavones diet). After 16 wk of consuming these diets, choline acetyltransferase (ChAT) activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…However, at higher concentrations, genistein inhibits tyrosine kinases (Akiyama et al, 1987), some of which are involved in long-term potentiation and cognitive function. Studies of the effects of soy isoflavones on cognitive function in men are as yet inconclusive (Lund et al, 2001;Lee et al, 2004). Therefore, it can be postulated that soy phytoestrogens may enhance cognitive function at low doses, but impair cognitive function when ingested in higher amounts.…”
Section: B Environmental Toxicantsmentioning
confidence: 99%
“…However, at higher concentrations, genistein inhibits tyrosine kinases (Akiyama et al, 1987), some of which are involved in long-term potentiation and cognitive function. Studies of the effects of soy isoflavones on cognitive function in men are as yet inconclusive (Lund et al, 2001;Lee et al, 2004). Therefore, it can be postulated that soy phytoestrogens may enhance cognitive function at low doses, but impair cognitive function when ingested in higher amounts.…”
Section: B Environmental Toxicantsmentioning
confidence: 99%
“…Isoflavone supplementation has been observed to have a favourable effect on cognitive function [13], particularly verbal memory, in postmenopausal women [51] and a 6 and 12-week supplementation was observed to have a positive effect of frontal lobe function [27]. Furthermore, animal studies have also indicated that isoflavones are capable of improving cognitive function [58,64,77]. However, there is still uncertainty regarding their effects as some large intervention trials have reported that isoflavone supplementation does not lead to cognitive improvements [30].…”
Section: Flavonoid-induced Improvements In Memory Learning and Cognimentioning
confidence: 99%
“…Dietary soy-derived phytoestrogens may affect learning and memory and alter the expression of proteins involved in neural protection and inflammation in rats (27). Soy isoflavones may also affect the cholinergic system of the brain and reduce age-related neuronal loss and cognition decline in male rats (28). There are proposed mechanisms for the neuroprotective effects of isoflavones.…”
Section: Effects Of Soy Isoflavones On Learning and Memorymentioning
confidence: 99%